Polyglycolic acid composition and preparation method thereof, product and preparation method thereof, and method for adjusting flow rate of polyglycolic acid melt
By melt blending multimodal polyglycolic acid B with unimodal polyglycolic acid A, the melt flow rate was adjusted, the crosslinking problem caused by chemical modification was solved, and a polyglycolic acid composition with low melt flow rate and good degradability was achieved.
Patent Information
- Application Number
- CN202310817644.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-07
AI Technical Summary
Existing methods for modifying polyglycolic acid to reduce its melt flow rate are all chemical modification methods, which result in partial cross-linking structures and may affect its degradation performance and reprocessing performance.
Polyglycolic acid B with a multi-peak molecular weight distribution and polyglycolic acid A with a uni-peak molecular weight distribution are melt-blended to adjust the melt flow rate, avoid chemical modification, and maintain the degradation performance of polyglycolic acid.
It enables the adjustment of low melt flow rate to meet different application requirements, reduce environmental pollution, and maintain good reprocessability and degradability.
Smart Images

Figure CN119264618A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer processing and modification technology, specifically to a polyglycolic acid composition and its preparation method, an article and its preparation method, and a method for adjusting the melt flow rate of polyglycolic acid. Background Technology
[0002] Polyglycolic acid (PGA) is a biodegradable polyester with excellent mechanical strength and gas barrier properties, as well as good biodegradability and biocompatibility, making it suitable for applications in biomedical materials, disposable packaging materials, barrier materials, and downhole tools. However, unmodified PGA in existing technologies has low melt strength and melt viscosity, and a relatively high melt flow rate, making it difficult to meet the requirements of applications such as blow molding and foaming that require lower melt flow rates.
[0003] CN112469765A (Shanghai Pujing Chemical Technology Co., Ltd.) discloses a novel composition comprising polyglycolic acid or a polyglycolic acid copolymer and filler. The melt index of the polyglycolic acid copolymer can be in the range of 0.1 to 1000 g / 10 min. In an embodiment of the invention, the melt flow rate (MFR) is reduced from 27 g / 10 min to 5 g / 10 min by adding an epoxy chain extender (ADR) and a metal passivator. However, since the added additives are reactive, it is a chemical modification, and the obtained product is a partially crosslinked product.
[0004] CN114075331A, CN114075332A, and CN114075378A (China Energy Investment Corporation) disclose several modified polyglycolic acid compositions. These compositions primarily involve chain extension modification of polyglycolic acid after polymerization with isocyanate, resulting in a significant increase in melt viscosity and a significant decrease in melt flow rate. However, similar to epoxy chain extenders, these are all chemical modifications, and unreacted isocyanate groups can further react with the -NH- functional groups of the generated urethane groups, leading to partial cross-linking of the product. Furthermore, isocyanates themselves possess a certain degree of toxicity, and their processing, use, and degradation can have a certain impact on the environment.
[0005] CN114075373A (China Energy Investment Corporation) discloses a modified polyglycolic acid composition, its preparation method, and its application. Specifically, it uses a polyolefin containing maleic anhydride as a modifier, and adds an antioxidant to give the modified polyglycolic acid composition a high thermal decomposition temperature, significantly improved stability at high temperatures, and increased melt viscosity, which is beneficial for processing and molding. However, similar to the aforementioned other comparative patents, this invention utilizes the reaction between maleic anhydride and the hydroxyl groups in polyglycolic acid, which is still a chemical modification, and the resulting modified polyglycolic acid composition is a partially cross-linked polymer.
[0006] CN115322303A (China Energy Investment Corporation) discloses a composition for preparing polyglycolic acid materials, a polyglycolic acid material, a method for preparing the same, and its applications. The polyglycolic acid composition is a cross-linked polyglycolic acid obtained by partially cross-linking polyglycolic acid with an initiator and a cross-linking agent. This method also changes the chemical structure of the polyglycolic acid itself. Summary of the Invention
[0007] As mentioned above, the existing methods for reducing the melt flow rate of polyglycolic acid by post-polymerization modification are all chemical modification methods, which change the chemical structure of polyglycolic acid itself and produce a partially cross-linked structure. The inventors have found that the existing chemical modification methods may have a certain impact on the reprocessing performance and degradation performance of polyglycolic acid.
[0008] The purpose of this invention is to overcome the problem that existing methods for modifying polyglycolic acid (PGA) after polymerization to reduce its melt flow rate are all chemical modification methods, and often involve introducing partially cross-linked structures, which may affect the degradation performance of PGA. Through extensive research, the inventors of this invention have discovered that without any chemical modification, simply by adding multi-peak PGA with a unique structure, the melt viscosity of unimodal PGA can be reduced, and its melt flow rate can be adjusted, making it suitable for a wider range of processing scenarios. In this process, no other chemical thickeners need to be added, reducing environmental pollution during preparation and use. Furthermore, since the main structure of PGA remains unchanged, it has no impact on its degradation properties.
[0009] Based on the above research, the first aspect of the present invention provides a polyglycolic acid composition, the composition comprising the following components:
[0010] (a) Polyglycolic acid B with a multimodal molecular weight distribution;
[0011] (b) Polyglycolic acid A with a unimodal molecular weight distribution.
[0012] A second aspect of the present invention provides a method for preparing the composition of the present invention, the method comprising: melt-blending the various components of the composition.
[0013] A third aspect of the present invention provides an article comprising the composition described herein.
[0014] A fourth aspect of the present invention provides a method for preparing an article, the method comprising: heat-treating and molding the composition of the present invention.
[0015] The fifth aspect of the present invention provides a method for adjusting the melt flow rate of polyglycolic acid, the method comprising: subjecting the components of the composition to a step including melt blending to adjust the melt flow rate of polyglycolic acid A in the composition to obtain modified polyglycolic acid.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects:
[0017] (1) In this invention, when the composition includes polyglycolic acid A with a single molecular weight distribution and polyglycolic acid B with a multi-peak molecular weight distribution, the composition can exist in the form of a polymer after a short period of melt blending, which has low requirements for equipment and process.
[0018] (2) By controlling the ratio of polyglycolic acid A to polyglycolic acid B, the overall melt flow rate of the composition can be easily adjusted to meet the melt flow rate requirements of different application fields. The products prepared using this composition can meet the requirements of different application fields.
[0019] (3) This invention is a physical modification and does not require the addition of other chemical thickeners, thus reducing environmental pollution during preparation and use.
[0020] (4) The present invention does not cause polyglycolic acid to form a cross-linked structure, and therefore does not affect the degradability of polyglycolic acid.
[0021] (5) The polyglycolic acid B of the present invention not only has high melt viscosity but also high melt strength, so the melt strength of the modified polyglycolic acid composition obtained therefrom will also be improved, thus better meeting the needs of processing fields such as blown film that require high melt strength. Attached Figure Description
[0022] Figure 1 These are GPC curves for Example 1, Example 3, and Comparative Example 1;
[0023] Figure 2 This is a curve showing the change in melt flow rate of modified polyglycolic acid (polyglycolic acid A) as a function of the amount of polyglycolic acid B in the comparative example. Detailed Implementation
[0024] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0025] Based on the above research, the first aspect of the present invention provides a polyglycolic acid composition, the composition comprising the following components:
[0026] (a) Polyglycolic acid B with a multimodal molecular weight distribution;
[0027] (b) Polyglycolic acid A with a unimodal molecular weight distribution.
[0028] In this invention, when the composition includes polyglycolic acid A with a unimodal molecular weight distribution and polyglycolic acid B with a multimodal molecular weight distribution, the composition can exist in the form of a polymer after a short period of melt blending. At the same time, by controlling the ratio of polyglycolic acid A to polyglycolic acid B, the overall melt flow rate of the composition can be well controlled to meet the melt flow rate requirements of different application fields. The products prepared using this composition can meet the needs of different application fields. In particular, the composition of this invention not only has good reprocessability, but also the products containing the composition of this invention have good degradability.
[0029] According to the present invention, in some embodiments, the polyglycolic acid B exhibits a bimodal or trimodal distribution in the GPC curve. By employing the aforementioned embodiments, the overall melt flow rate of the composition can be better controlled to meet the melt flow rate requirements of different application areas.
[0030] According to the present invention, in some embodiments, in the GPC curve, at least one peak of the polyglycolic acid B has a weight-average molecular weight greater than 1 million g / mol, and a peak area percentage of not less than 0.5%, for example, 0.5%, 1.0%, 2.0%, 3.0%, 4.7%, 5.0%, 6.0%, 8.0%, 9.4%, or 10.0%, and any range of the above values, preferably not less than 1.0%, more preferably 1.5% to 10.0%. By employing the aforementioned embodiments, the overall melt flow rate of the composition can be better controlled to meet the melt flow rate requirements of different application fields, while also giving the composition of the present invention good reprocessability, and articles containing the composition of the present invention also have good degradability.
[0031] According to the present invention, in some embodiments, the weight-average molecular weight of at least one peak in the multiple peaks of polyglycolic acid B in the GPC curve is 150,000 to 500,000 g / mol. Using the foregoing embodiments, polyglycolic acid B can function as a tackifier, and a composition existing in polymer form can be obtained by a simple method. Furthermore, articles containing the compositions of the present invention exhibit good degradability.
[0032] According to some preferred embodiments of the present invention, when the polyglycolic acid B exhibits a bimodal distribution, the weight-average molecular weight of the first peak in the bimodal distribution of the polyglycolic acid B is greater than 1 million g / mol, and the peak area ratio of the first peak is not less than 0.5%, preferably not less than 1.0%, and more preferably 1.5% to 10.0%; the weight-average molecular weight of the second peak in the bimodal distribution of the polyglycolic acid B is 150,000 to 500,000 g / mol, and the proportion is not less than 50%, preferably not less than 90.0%, and more preferably 90.0% to 98.5%.
[0033] According to the present invention, in some preferred embodiments, when the polyglycolic acid B exhibits a three-peak distribution, the weight-average molecular weight of the first peak of the three peaks of the polyglycolic acid B is greater than 1 million g / mol, and the peak area ratio of the first peak is not less than 0.5%, preferably not less than 1.0%, and more preferably 1.5% to 10.0%; the weight-average molecular weight of the second peak of the three peaks of the polyglycolic acid B is not less than 500,000 g / mol, and the proportion is not less than 10%, preferably 510,000 to 1,000,000 g / mol, and the proportion is 20% to 40%; the weight-average molecular weight of the third peak of the three peaks of the polyglycolic acid B is 150,000 to 500,000 g / mol, and the proportion is not less than 50%, preferably 50% to 70%.
[0034] According to the present invention, in some embodiments, the weight-average molecular weight of the polyglycolic acid A is 150,000 to 250,000 g / mol.
[0035] According to the present invention, in some embodiments, under the test conditions of 230°C / 2.16kg, the melt mass flow rate (MFR1) of polyglycolic acid A is 20–90 g / 10 min.
[0036] In this invention, the molecular weight is determined using gel permeation chromatography (GPC), a conventional method in the art. The ordinate and abscissa of the GPC curve are related to the polymer's mass and molecular weight, respectively. Therefore, integrating the curve yields the corresponding component mass; that is, the ratio of the integrated peak area to the total integrated peak area is the corresponding mass ratio, calculated from the GPC curve integrated area ratio. In this invention, the GPC test is performed on an Anglientan PL-GPC50 gel permeation chromatograph (USA), and the processing software is GPC offline. During the test, the mobile phase is hexafluoroisopropanol containing 5 mmol / L sodium trifluoroacetate, the flow rate is 1 mL / min, the column temperature is 40℃, the injection volume is 100 μL, the standard is PMMA, and the sample concentration is 1 mg / mL.
[0037] According to the present invention, in some embodiments, under test conditions of 230°C / 2.16 kg, the melt flow rate (MFR2) of the polyglycolic acid B is 0.1–10 g / 10 min, for example, 0.1 g / 10 min, 0.5 g / 10 min, 1 g / 10 min, 2.2 g / 10 min, 3.5 g / 10 min, 5 g / 10 min, 7 g / 10 min, 9 g / 10 min, 10 g / 10 min, and any combination of two of the above values, preferably 0.5–5.0 g / 10 min. Using the aforementioned embodiments, the synergistic effect of polyglycolic acid A and polyglycolic acid B can obtain compositions that meet the melt flow rate requirements of different application fields, and articles containing the compositions of the present invention have good degradability.
[0038] In this invention, the melt flow rate (MFR) of the polymer was tested on a CEAST MF20 melt flow rate tester from Instron Corporation in the United States. The test temperature was 230°C, the load weight was 2.16 kg, and the preheating time was 4 min.
[0039] In this invention, the melt strength test of the polymer was conducted on a Rosand RH7 high-pressure capillary rheometer from Malvern Panaco in China, with a Haul Off model (diameter: 2.0 mm, length: 20 mm). The barrel pusher was pressed down at a speed of 15 mm / min, the test temperature was 235°C, the initial drafting speed of the take-up roller was 3 m / min, the final drafting speed was 50 m / min, the speed was increased uniformly over a period of 3 minutes, and 30 data points were collected evenly.
[0040] According to the present invention, in some embodiments, the polyglycolic acid B comprises a polyglycolic acid graft copolymer and a polyglycolic acid homopolymer. Using the aforementioned embodiments, the synergistic effect of polyglycolic acid A and polyglycolic acid B can yield compositions that meet the melt flow rate requirements of different application fields, and articles containing the compositions of the present invention have good degradability.
[0041] According to the present invention, in some preferred embodiments, at least one peak of the polyglycolic acid B multipeaks is a polyglycolic acid graft copolymer. Using the foregoing embodiments, the compositions of the present invention can exhibit lower melt flow rates and reduce time-consuming technical cycles.
[0042] According to the present invention, in some preferred embodiments, one of the peaks in the polyglycolic acid B is a polyglycolic acid homopolymer. Using the foregoing embodiments, the compositions of the present invention can exhibit lower melt flow rates and reduced time-consuming process cycles, making them suitable for the efficient and economical production of articles for various applications.
[0043] According to some preferred embodiments of the present invention, when the polyglycolic acid B exhibits a bimodal distribution, the first peak of the bimodal distribution of the polyglycolic acid B is a polyglycolic acid graft copolymer, and the second peak is a polyglycolic acid homopolymer.
[0044] According to the present invention, in some other preferred embodiments, when the polyglycolic acid B exhibits a three-peak distribution, the first and second peaks of the bimodal distribution of the polyglycolic acid B are each independently polyglycolic acid graft copolymers, and the third peak is a polyglycolic acid homopolymer.
[0045] According to the present invention, in some embodiments, the polyglycolic acid graft copolymer comprises ethylene-vinyl alcohol copolymer segments and / or polyvinyl alcohol segments as its main chain, and glycolic acid monomer derivatives, glycolic acid oligomers, or glycolic acid polymers as its side chains. Using the aforementioned embodiments, polyglycolic acid B exhibits better thickening properties, and the composition obtained by its synergistic effect with polyglycolic acid A can exhibit a lower melt flow rate, reducing time and cycle time. Such compositions are suitable for the efficient and economical production of articles for various applications.
[0046] In this invention, the term "glycolic acid monomer derivative" refers to a polymer chain segment containing glycolic acid structural units; "glycolic acid oligomer" refers to a polymer with glycolic acid as a repeating unit, and the number of glycolic acid repeating units is relatively small; "glycolic acid polymer" refers to a polymer with glycolic acid as a repeating unit, and the number of glycolic acid repeating units is relatively large.
[0047] According to some preferred embodiments of the present invention, the structure of the polyglycolic acid graft copolymer is as shown in formula (I):
[0048]
[0049] In equation (Ⅰ), x and m are both positive integers, and y1, y2 and z are all natural numbers.
[0050] According to the present invention, in some preferred embodiments, in (I), the sum of x, y1, y2 and z is not less than 50, preferably 50 to 6000, and more preferably 200 to 2500. Using the aforementioned embodiments, polyglycolic acid B has a better thickening effect, and the composition obtained by its synergistic effect with polyglycolic acid A can exhibit a lower melt flow rate, reducing the time cycle. Such compositions are suitable for the efficient and economical production of articles in different application fields.
[0051] According to the present invention, in some embodiments, m in formula (I) is not less than 50, preferably 50 to 1000. Using the aforementioned embodiments, polyglycolic acid B has a better thickening effect, and the composition obtained by its synergistic effect with polyglycolic acid A can exhibit a lower melt flow rate, reducing the time cycle. Such compositions are suitable for the efficient and economical production of articles for various applications.
[0052] According to the present invention, in some embodiments, in formula (Ⅰ), z accounts for 0 to 50% of x+y1+y2+z.
[0053] According to the present invention, in some embodiments, in formula (Ⅰ), y1 accounts for 0 to 32% of x+y1+y2.
[0054] In this invention, it is understood that in formula (Ⅰ), when z is 0, the main chain of the polyglycolic acid graft copolymer is a polyvinyl alcohol segment, and in some preferred embodiments, when the main chain of the polyglycolic acid graft copolymer is a polyvinyl alcohol segment, the proportion of y1 to x+y1+y2 is 1 to 32%.
[0055] In this invention, it is understood that when y1 is 0, the main chain of the polyglycolic acid graft copolymer is an ethylene-vinyl alcohol copolymer segment, and in some preferred embodiments, when the main chain of the polyglycolic acid graft copolymer is an ethylene-vinyl alcohol copolymer segment, the proportion of z to x+y1+y2+z is 1-50%, preferably 20-45%, and the proportion of y1 to x+y1+y2 is 0-6%.
[0056] According to the present invention, the sum of x+y1+y2+z is the degree of polymerization of the ethylene-vinyl alcohol copolymer (and / or polyvinyl alcohol), which can be calculated from the number average molecular weight of the raw material ethylene-vinyl alcohol copolymer (and / or polyvinyl alcohol) and is related to the ethylene content in the ethylene-vinyl alcohol copolymer (and / or polyvinyl alcohol); while the ratio of x to y2 can be calculated from the integral area of the corresponding peak in the 1H NMR spectrum.
[0057] According to the present invention, the degree of alcoholysis of ethylene-vinyl alcohol copolymer (and / or polyvinyl alcohol) is a known parameter at the time of raw material delivery, and can also be detected by various detection methods in the art such as nuclear magnetic resonance and near-infrared spectroscopy.
[0058] According to the present invention, if the structure of the starting ethylene-vinyl alcohol copolymer (and / or polyvinyl alcohol) macromolecular initiator is known, then m = (number-average molecular weight of the high molecular weight portion of PGA - number-average molecular weight of the macromolecular initiator (ethylene-vinyl alcohol copolymer (and / or polyvinyl alcohol))) / (x*58). If the graft copolymer structure of the high molecular weight PGA described in this invention is obtained directly, it can be fully hydrolyzed first, the initiator collected, its structure analyzed, and then tested according to the above method. According to the exemplary embodiments described below, the calculated m in the obtained polymer is always greater than 50.
[0059] According to some preferred embodiments of the present invention, the structure of the polyglycolic acid homopolymer is as shown in formula (II):
[0060]
[0061] In equation (II), M1, M2, ..., M i Each independently Or -O-, n1, n2, ..., n i Each is an independent natural number, and at least one is not 0, i is an integer not less than 1, R is H, alkane or aromatic hydrocarbon, X is any chain segment, X is any chain segment, and X is preferably an alkyl or aromatic group with no more than 20 H or C atoms.
[0062] Using the aforementioned embodiments, polyglycolic acid B has a better thickening effect, and the composition obtained by the synergistic effect of polyglycolic acid A can exhibit a lower melt flow rate and reduce the time cycle. Such compositions are suitable for the efficient and economical production of products in different application fields.
[0063] According to some preferred embodiments of the present invention, when i is 1 in formula (II), R is H, alkane group or aromatic group.
[0064] According to the present invention, in some preferred embodiments, when i is greater than 1 in formula (II), R is an alkane group or an aromatic group with a molecular weight of 14 to 1000 g / mol.
[0065] In this invention, "alkane group" can be either branched alkane group or branched alkane group, and this invention does not have any special restrictions on this.
[0066] According to the present invention, in some preferred embodiments, in formula (II), i is an integer between 1 and 20, for example, 1, 2, 3, 4, 5, 6, 8, 9, 10, 13, 18 or 20, and any range of two of the above values, preferably an integer between 2 and 6.
[0067] According to some preferred embodiments of the present invention, in formula (II), n1, n2, ..., n i The sum is not less than 100, for example, 100, 500, 1500, 2000, 3000, 4000 or 5000, and any of the above values in the range of 100 to 5000.
[0068] In this invention, n1, n2, ..., n in equation (II) i Each has a wide range of choices, and their respective values are difficult to calculate. According to the present invention, n1, n2, ..., n i The sum of the values can be calculated by dividing the number-average molecular weight of the lower molecular weight peak in the GPC results by the molecular weight of the PGA repeating unit.
[0069] In a more preferred embodiment of the invention, relative to 100 parts by mass of polyglycolic acid segments The polyglycolic acid B contains 0.01 to 1 part by weight of ethylene-vinyl alcohol copolymer and / or polyvinyl alcohol segments. Contains 0.01 to 1 part by weight The mass content of each of the above segments can be detected using methods known in the art, or it can be calculated by the amount of material fed during the preparation process.
[0070] According to the present invention, the preparation method of polyglycolic acid B is not particularly limited as long as the purpose of the present invention can be achieved. In some embodiments, the preparation method of polyglycolic acid B includes: in the presence of a catalyst, polymerizing a polymer capable of obtaining polyglycolic acid segments. The monomer, ethylene-vinyl alcohol copolymer and / or polyvinyl alcohol, and optionally a small molecule co-initiator, and optionally an antioxidant are melt-polymerized.
[0071] Under the current process, since an anhydrous and oxygen-free environment cannot be guaranteed, even without adding small molecule co-initiators, moisture in the air can also act as an initiator. In this case, in formula (II), M is O, R is H, and i = 1.
[0072] According to the present invention, the selection of monomers in the preparation method of polyglycolic acid B is not particularly limited as long as the purpose of the present invention can be achieved. In some preferred embodiments, the monomers include at least one of methyl glycolate, glycolic acid and glycolide, preferably glycolide.
[0073] According to the present invention, the selection of the ethylene-vinyl alcohol copolymer is not particularly limited as long as the purpose of the present invention can be achieved. In some embodiments, the content of ethylene segments in the ethylene-vinyl alcohol copolymer is 25 to 50 mol%, for example, 25 mol%, 35 mol%, 45 mol%, or 50 mol%, and any range of two of the above values.
[0074] According to the present invention, in some embodiments, the degree of polymerization of the ethylene-vinyl alcohol copolymer is 50 to 6000, for example, 50, 300, 500, 1000, 1500, 2000, 3000, 4000, 5000 or 6000, and any range of any two of the above values, preferably 300 to 2000, and any two values and any range.
[0075] According to some embodiments of the present invention, the melt flow rate of the ethylene-vinyl alcohol copolymer at 190°C / 2.16 kg is 0.1 to 50 g / 10 min.
[0076] In the embodiments of the present invention, an ethylene-vinyl alcohol copolymer with an ethylene content of 38 mol% and a melt flow rate of 1.7 g / 10 min under the conditions of 190 °C / 2.16 kg is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.
[0077] According to the present invention, the degree of hydrolysis of the polyvinyl alcohol can be selected within a wide range. In a preferred embodiment of the present invention, the degree of hydrolysis of the polyvinyl alcohol is 68-99%.
[0078] According to the present invention, the degree of polymerization of the polyvinyl alcohol can be selected within a wide range. In a preferred embodiment of the present invention, the degree of polymerization is 100 to 6000, preferably 300 to 2000. For example, it can be 300, 500, 1000, 1500, 2000, as well as any two values and any range of two values.
[0079] In the embodiments of the present invention, polyvinyl alcohol with a degree of polymerization of 500 and a degree of hydrolysis of 88% is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.
[0080] According to the present invention, as long as the purpose of the present invention can be achieved, there is no special limitation on the type of small molecule co-initiator. In some embodiments, the small molecule co-initiator is a small molecule containing hydroxyl or amino groups with a boiling point greater than 160°C, preferably with a molecular weight not greater than 1000 g / mol; more preferably 60 to 300 g / mol.
[0081] According to the present invention, in some embodiments, the structure of the small molecule co-initiator is as shown in formula (a):
[0082]
[0083] In equation (a), R, M1, M2, ..., M i The definition is the same as that in equation (II).
[0084] In this invention, small molecule co-initiators that can be listed include ethylene glycol, butanediol, glycerol, serine, leucine, pentaerythritol, sorbitol, xylitol, amino acids, phenol, hydroquinone, resorcinol, benzyl alcohol, aniline, benzylamine, p-phenylenediamine, m-phenylenediamine, hexamethylenediamine, dodecanediamine, etc. In the embodiments of this invention, 1,4-butanediol is used as an example to illustrate the advantages of this invention, but this invention is not limited thereto.
[0085] According to the present invention, the type of catalyst is not particularly limited as long as the purpose of the present invention can be achieved. In some embodiments, the catalyst is selected from salt compounds corresponding to at least one of transition metal elements, group IIA metal elements, group IIIA metal elements, group IVA metal elements and group VA metal elements, and / or organic guanidine catalysts.
[0086] According to some preferred embodiments of the present invention, the catalyst is a salt compound corresponding to at least one of Sn, Bi, Mg, Al, Ca, Fe, Mn, Ti and Zn, preferably a Sn salt.
[0087] In this invention, the raw material may be "optionally" present or absent.
[0088] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of ethylene-vinyl alcohol copolymer (and / or polyvinyl alcohol) used in the preparation of polyglycolic acid B is not particularly limited. In some embodiments, the amount of ethylene-vinyl alcohol copolymer (and / or polyvinyl alcohol) used is 0.001 to 10 parts by mass relative to 100 parts of monomer, preferably 0.01 to 1 part.
[0089] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of catalyst used in the preparation of polyglycolic acid B is not particularly limited. In some embodiments, the amount of catalyst used is 0.005 to 1 part by mass relative to 100 parts of monomer, preferably 0.01 to 0.2 parts.
[0090] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the small molecule co-initiator used in the preparation of polyglycolic acid B is not particularly limited. In some embodiments, the amount of the small molecule co-initiator is 0.001 to 10 parts by mass relative to 100 parts of monomer, preferably 0.01 to 1 part.
[0091] According to the present invention, as long as the purpose of the present invention can be achieved, there is no particular limitation on the amount of antioxidant used in the preparation of polyglycolic acid B. In some embodiments, the amount of antioxidant used is 0 to 2 parts by mass relative to 100 parts of monomer, preferably 0.01 to 1 part.
[0092] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions for melt polymerization in the preparation of polyglycolic acid B are not particularly limited. In some embodiments, the conditions for the melt polymerization reaction include a temperature of 160-250°C, preferably 200-240°C.
[0093] According to the present invention, in some embodiments, the conditions for the melt polymerization reaction include: a reaction time of 0.5 to 60 min, preferably 1 to 10 min.
[0094] According to the present invention, the apparatus for melt polymerization in the preparation of polyglycolic acid B is not particularly limited, and the apparatus that can be listed includes one or more of the following in series: tubular reactor, internal mixer, Farrel continuous mixer, Banbury mixer, single screw extruder, multi-screw extruder and reciprocating single screw extruder. Preferably, it is an internal mixer, a single screw extruder or a twin screw extruder, and more preferably a twin screw extruder.
[0095] According to the present invention, when using twin-screw extrusion for melt polymerization, the screw speed and feeding speed can be controlled as needed, for example, the screw speed can be controlled at 50 to 70 rpm and the feeding speed can be controlled at 10 to 30 kg / h.
[0096] According to the present invention, in the preparation of polyglycolic acid B, after melt polymerization, extrusion, cooling granulation, and devolatilization can be performed as needed; wherein, during devolatilization, vacuum devolatilization at 160-190°C (e.g., 180°C) for 0.5-3.0 h followed by cooling in a protective atmosphere (e.g., nitrogen) can be selected.
[0097] According to the present invention, in some embodiments, under test conditions of 230°C / 2.16 kg, the melt flow rate (MFR3) of the composition is 0.1–30 g / 10 min, preferably 3–15 g / 10 min. In the present invention, the interaction between polyglycolic acid A and polyglycolic acid B can yield compositions with different melt flow rate requirements.
[0098] In this invention, compositions containing polyglycolic acid A and polyglycolic acid B exhibit lower melt flow rates, reducing time and cycle time. Such compositions are suitable for the efficient and economical production of articles for various applications. Therefore, in some embodiments, under test conditions of 230°C / 2.16 kg, the ratio of the melt flow rate MFR1 of the polyglycolic acid A to the melt flow rate MFR3 of the composition is not less than 1.2, preferably not less than 3.0.
[0099] According to the present invention, in some embodiments, the mass ratio of polyglycolic acid B to polyglycolic acid A is 5:95 to 90:10, for example, 5:95, 15:85, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, or 90:10, and any range of two of the above ratios, preferably 20:80 to 60:40. Using the foregoing embodiments, the compositions of the present invention can exhibit lower melt flow rates and reduce time-consuming technical cycles. Such compositions are suitable for the efficient and economical production of articles for various applications.
[0100] According to the present invention, some additives that are conventionally available in the art may also be present in the compositions of the present invention as optional additives, wherein optional additives include stabilizing additives such as antioxidants, metal passivators (ester exchange inhibitors) and anti-hydrolysis agents, as well as adhesive and dispersing additives such as white oil.
[0101] According to the present invention, in some embodiments, the composition optionally contains an antioxidant component, preferably the antioxidant to the total mass ratio of polyglycolic acid A and polyglycolic acid B is 0.01 to 3, more preferably 0.1 to 1.0.
[0102] According to the present invention, as long as the purpose of the present invention can be achieved, the type of antioxidant is not particularly limited. Conventional hindered phenolic antioxidants and / or phosphite antioxidants in the art can be used, such as antioxidant 1010, antioxidant 1024, antioxidant 1098, antioxidant 1076, antioxidant 168, antioxidant 686, antioxidant 626, etc. The above different types of antioxidants can be used alone or in combination.
[0103] According to the present invention, in some embodiments, the composition optionally contains a metal passivating agent (ester exchange inhibitor) component, preferably the total mass ratio of the metal passivating agent (ester exchange inhibitor) to polyglycolic acid A and polyglycolic acid B is 0.1 to 3.0, more preferably 0.1 to 0.7.
[0104] According to the present invention, there is no particular limitation on the specific type of metal passivating agent (ester exchange inhibitor) as long as the purpose of the present invention can be achieved. In the embodiments of the present invention, stabilizer AX-71 is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.
[0105] According to the present invention, in some embodiments, the composition optionally contains an anti-hydrolysis agent component, preferably the total mass ratio of the anti-hydrolysis agent to polyglycolic acid A and polyglycolic acid B is 0.1 to 5.0, more preferably 0.3 to 3.0.
[0106] According to the present invention, the specific type of anti-hydrolysis agent is not particularly limited as long as the purpose of the present invention can be achieved. In the embodiments of the present invention, anti-hydrolysis agent S9000 is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.
[0107] According to the present invention, in some embodiments, the composition further contains white oil, preferably the total mass ratio of the white oil to polyglycolic acid A and polyglycolic acid B is 0.1 to 5.0, more preferably 0.3 to 3.0.
[0108] In this invention, preferably, the composition is present in the form of a polymer.
[0109] A second aspect of the present invention provides a method for preparing the composition of the present invention, the method comprising: melt-blending the various components of the composition.
[0110] According to the present invention, in some embodiments, the melt blending conditions include a blending temperature of 220–260°C.
[0111] According to the present invention, in some embodiments, the melt blending conditions include a blending time of 0.5 to 10 min, preferably 2 to 6 min.
[0112] According to the present invention, the apparatus for melt blending can be any conventional apparatus in the art, such as a twin-screw extruder, as long as it can achieve the purpose of the present invention.
[0113] According to the present invention, in equipment requiring stepped heating, such as a twin-screw extruder, the aforementioned melt mixing temperature refers to the highest temperature set in the multi-stage heating process.
[0114] According to the present invention, when the equipment is a twin-screw extruder, the mixing time is the residence time of the raw material in the twin-screw extruder, which can be determined by methods known in the art, such as, but not limited to, the following: using black masterbatch as a marker, the residence time is the time from when the black masterbatch enters the screw to when the material exits the die with the darkest color.
[0115] According to the present invention, as long as the purpose of the present invention can be achieved, when using a twin-screw extruder for melt blending, there are no special restrictions on the screw speed of the twin-screw extruder and the feed rate of the raw material. For example, the screw speed of the twin-screw extruder is 80 to 120 rpm and the feed rate of the raw material is 1 to 5 kg / h.
[0116] Existing modified polyglycolic acid polymers are generally modified using chemical modification methods, while the composition of this invention exists in the form of a polymer, specifically, it can be in the form of sheets, films, powders, granules, or spheres. This composition not only has a low melt flow rate but also good reprocessability and degradability.
[0117] According to the present invention, it is understood that the melt blending process can be followed by molding as needed.
[0118] In this invention, the compositions of this invention can be provided in particulate or spherical form, and as an upstream product, the compositions can be further used to obtain downstream products with low melt flow rates, good reprocessability and degradability. Based on this, a third aspect of this invention provides an article comprising the compositions of this invention.
[0119] According to the present invention, the products of the present invention include biodegradable packaging bags, pharmaceutical packaging films, food preservation films, agricultural films, barrier containers, foaming materials, and polyglycolic acid fibers, etc.
[0120] In this invention, the composition of this invention is heat-treated for further use. Based on this, a fourth aspect of this invention provides a method for preparing an article, the method comprising: heat-treating the composition of this invention and molding it.
[0121] According to the present invention, the heat treatment can be carried out in a manner conventional in the art, such as melting it to obtain a molten composition.
[0122] According to the invention, the skill is performed by any suitable means in the art, such as injecting the molten composition into a mold.
[0123] According to the present invention, taking the product as a film product, the specific preparation method of the film product includes: adding the composition of the present invention into at least one screw extruder, melting and compressing it, then extruding it through a film forming die, cooling, stretching, and winding it to obtain the film product.
[0124] Based on the inventive concept of the present invention, a fifth aspect of the present invention provides a method for adjusting the melt flow rate of polyglycolic acid, the method comprising: subjecting the components in the composition to a step including melt blending to adjust the melt flow rate of polyglycolic acid A in the composition to obtain modified polyglycolic acid.
[0125] In this invention, the method provided is a simple and easy-to-implement physical modification method with low requirements for equipment and processes. Polyglycolic acid B is used to adjust the melt flow rate of polyglycolic acid A. Polyglycolic acid B acts as a thickener added to polyglycolic acid A, and after a short period of melt blending, modified polyglycolic acid with a low melt flow rate is obtained. Furthermore, the overall melt flow rate of the modified polyglycolic acid can be controlled by adjusting the amount of thickener added and other conditions to meet the melt flow rate requirements of different application fields. The resulting modified polyglycolic acid exhibits good processability.
[0126] According to the present invention, it is understood that the compositions of the present invention may exist in the form of modified polyglycolic acid.
[0127] The present invention will be described in detail below through embodiments. In the following examples, glycolide was purchased from Shenzhen Boli Biomaterials Co., Ltd., with a purity ≥99.5%; stannous octoate and 1,4-butanediol were both purchased from Sinopharm Chemical Reagent Co., Ltd., with stannous octoate having an AR purity and 1,4-butanediol having a CP purity; antioxidant 1010 was purchased from BASF (China) Co., Ltd., and antioxidant 608, anti-hydrolysis agent S900, and stabilizer S9000 were all purchased from Shanghai Puzhan Industrial Selection Co., Ltd.; ethylene-vinyl alcohol copolymer (EVOH) was purchased from Kuraray Co., Ltd. of Japan, with the brand name EVALTM H171B, an ethylene content of 38 mol%, and a melt flow rate of 1.7 g / 10 min at 190℃ / 2.16 kg; polyvinyl alcohol (PVA) was purchased from Chongqing Chuanwei Chemical Co., Ltd. of China Petrochemical Corporation, with the brand name 0588, a degree of polymerization of 500, and a degree of alcoholysis of 88%; and white oil (ISO VG) was also purchased. 46), purchased from SKALN Group Ltd., France; Polyglycolic acid A, purchased from Shenzhen Boli Biomaterials Co., Ltd.; other raw materials were commercially available.
[0128] In the following examples and comparative examples:
[0129] The melt flow rate of modified polyglycolic acid (polyglycolic acid A) as a function of the amount of polyglycolic acid B is shown in the figure below. Figure 2 As shown.
[0130] Example 1
[0131] Preparation of polyglycolic acid B:
[0132] Ethyl glycol, stannous octoate, ethylene-vinyl alcohol copolymer (EVOH), 1,4-butanediol, antioxidant 1010, antioxidant 608, and anti-hydrolysis agent S9000 were mixed evenly in a mass ratio of 100:0.04:0.02:0.03:0.3:0.3:0.5, and then reacted and extruded using a Koya parallel co-rotating twin-screw extruder (screw diameter: 50 mm, length-to-diameter ratio: 56). After cooling and granulation, the mixture was then processed in 1... Polyglycolic acid B was obtained by solid-phase vacuum devolatilization at 80℃ for 2 hours and cooling under nitrogen protection. The extruder has 14 sections from the feed inlet to the die. The first section only serves as the feeding section and cannot be heated. The temperatures of sections 2-13 and the die are set as follows: 50℃, 150℃, 190℃, 190℃, 190℃, 190℃, 190℃, 200℃, 200℃, 210℃, 210℃, and 210℃, respectively. The twin-screw extruder has a screw speed of 60 rpm, a feed rate of 20 kg / h, and a residence time of approximately 6 minutes.
[0133] Polyglycolic acid B particles were collected and characterized for molecular weight using GPC. The molecular weight distribution of polyglycolic acid B showed a bimodal distribution in the GPC curve. The overall weight-average molecular weight was 341,000 g / mol, and the molecular weight distribution index was 3.0. Among them, the weight-average molecular weight of the graft copolymer was 2,797,500 g / mol, the molecular weight distribution index was 1.3, and the mass percentage was 9.4%. The weight-average molecular weight of the homopolymer was 189,800 g / mol, the molecular weight distribution index was 1.8, and the mass percentage was 90.6%.
[0134] Melt flow rate tests on the polyglycolic acid B particles showed a flow rate of 2.2 g / 10 min at 230℃ and 2.16 kg. Melt strength tests on the polyglycolic acid B particles showed a melt strength of approximately 15 cN at 235℃.
[0135] Preparation of modified polyglycolic acid: Polyglycolic acid A (Comparative Example 2), the above-mentioned polyglycolic acid B, white oil, antioxidant 1010, antioxidant 608, anti-hydrolysis agent S9000 and stabilizer AX-71 were mixed evenly in a mass ratio of 80:20:0.8:0.3:0.3:0.5:0.2, and then extruded and granulated using a Labtech parallel co-rotating twin-screw extruder (screw diameter: 20 mm, length-to-diameter ratio: 40) to obtain modified polyglycolic acid. The extruder consists of 11 sections from the feed inlet to the die, numbered 1 to 11. Section 1 is only used for feeding and cannot be heated. The temperatures of sections 2 to 11 of the extruder are 160℃, 200℃, 240℃, 240℃, 240℃, 240℃, 240℃, 235℃, and 235℃, respectively, with a residence time of approximately 2.5 minutes. The screw speed of the twin-screw extruder is 100 rpm, and the feeding speed is 3 kg / h.
[0136] The molecular weight of the modified polyglycolic acid was characterized by GPC, and the analytical results are shown in Table 1. The GPC curves are shown in the figure below. Figure 1 As shown.
[0137] The melt flow rate of the modified polyglycolic acid was characterized under the following conditions: 230℃ / 2.16kg. The melt flow rate (MFR3) of the modified polyglycolic acid was 10.8 ± 1.6 g / 10 min, and the MFR1 / MFR3 ratio was 4.63, where MFR1 is the melt flow rate of polyglycolic acid A. The melt strength of the modified polyglycolic acid was also tested. At 235℃, its melt strength was approximately 1.5 cN, representing an increase of about 15 times.
[0138] Example 2
[0139] The method is the same as in Example 1, except that the mass ratio of polyglycolic acid A to polyglycolic acid B is 60:40; otherwise, it is the same as in Example 1.
[0140] The molecular weight of the modified polyglycolic acid was characterized by GPC, and the results are shown in Table 1.
[0141] The melt flow rate of the modified polyglycolic acid was characterized under the following conditions: 230℃ / 2.16kg. The melt flow rate (MFR3) of the modified polyglycolic acid was 6.6 ± 0.9 g / 10 min, and the MFR1 / MFR3 ratio was 7.58, where MFR1 is the melt flow rate of polyglycolic acid A. The melt strength of the modified polyglycolic acid was also tested. At 235℃, its melt strength was approximately 3 cN, representing an increase of about 30 times.
[0142] Example 3
[0143] The method of Example 1 is the same, except that the mass ratio of polyglycolic acid A to polyglycolic acid B is 40:60; otherwise, it is the same as in Example 1.
[0144] The molecular weight of the modified polyglycolic acid was characterized by GPC, and the analytical results are shown in Table 1. The GPC curves are shown in the figure below. Figure 1 As shown.
[0145] The melt flow rate of the modified polyglycolic acid was characterized under the following conditions: 230℃ / 2.16kg. The melt flow rate (MFR3) of the modified polyglycolic acid was 5.9 ± 0.6 g / 10 min, and the MFR1 / MFR3 ratio was 8.47, where MFR1 is the melt flow rate of polyglycolic acid A. The melt strength of the modified polyglycolic acid was also tested. At 235℃, its melt strength was approximately 4 cN, representing an increase of about 40 times.
[0146] Example 4
[0147] Preparation of polyglycolic acid B: Ethyl glycolide, stannous octoate, polyvinyl alcohol (PVA), 1,4-butanediol, antioxidant 1010, antioxidant 608, and anti-hydrolysis agent S9000 were mixed evenly in a mass ratio of 100:0.04:0.015:0.03:0.3:0.3:0.5. The mixture was then extruded and granulated using a Labtech parallel co-rotating twin-screw extruder (screw diameter: 20 mm, length-to-diameter ratio: 40) to obtain polyglycolic acid. B; The extruder consists of 11 sections from the feed inlet to the die, numbered 1 to 11. Section 1 only serves to feed material and cannot be heated. The temperatures of sections 2 to 11 of the extruder are 160℃, 200℃, 240℃, 240℃, 240℃, 240℃, 240℃, 235℃, and 235℃, respectively. The screw speed of the twin-screw extruder is 120 rpm, the feeding speed is 3 kg / h, and the residence time is approximately 2 minutes.
[0148] Polyglycolic acid B particles were collected and characterized for molecular weight using GPC. The molecular weight distribution of polyglycolic acid B showed a bimodal distribution in the GPC curve. The overall weight-average molecular weight was 299,700 g / mol, and the molecular weight distribution index was 2.7. Among them, the weight-average molecular weight of the graft copolymer was 246,540 g / mol, the molecular weight distribution index was 1.2, and the mass percentage was 4.7%. The weight-average molecular weight of the homopolymer was 179,700 g / mol, the molecular weight distribution index was 1.7, and the mass percentage was 95.3%.
[0149] Melt flow rate tests on the polyglycolic acid B particles showed a flow rate of 4.1 g / 10 min at 230℃ and 2.16 kg. Melt strength tests on the polyglycolic acid B particles showed a melt strength of approximately 12 cN at 235℃.
[0150] Preparation of modified polyglycolic acid: Polyglycolic acid A (Comparative Example 2), the above-mentioned polyglycolic acid B, white oil, antioxidant 1010, antioxidant 608, anti-hydrolysis agent S9000 and stabilizer AX-71 were mixed evenly in a mass ratio of 70:30:0.8:0.3:0.3:0.5:0.2. The mixture was then extruded and granulated using a Labtech parallel co-rotating twin-screw extruder (screw diameter: 20 mm, length-to-diameter ratio: 40) to obtain modified polyglycolic acid. The extruder consists of 11 sections from the feed inlet to the die, numbered 1 to 11. Section 1 is only used for feeding and cannot be heated. The temperatures of sections 2 to 11 of the extruder are 160℃, 200℃, 240℃, 240℃, 240℃, 240℃, 240℃, 240℃, 235℃, and 235℃, respectively. The residence time is approximately 2.5 minutes. The screw speed of the twin-screw extruder is 100 rpm, and the feeding speed is 3 kg / h.
[0151] The melt flow rate of the modified polyglycolic acid was characterized under the following conditions: 230℃ / 2.16kg. The melt flow rate (MFR3) of the modified polyglycolic acid was 11.4 ± 1.5 g / 10 min, and the MFR1 / MFR3 ratio was 4.39, where MFR1 is the melt flow rate of polyglycolic acid A. The melt strength of the modified polyglycolic acid was also tested. At 235℃, its melt strength was approximately 1.5 cN, representing an increase of about 15 times.
[0152] Example 5
[0153] Preparation of polyglycolic acid B: The preparation follows Example 1, except that 1,4-butanediol is not added, EVOH is replaced with polyvinyl alcohol (PVA), and the ratio of glycolide, stannous octoate, polyvinyl alcohol (PVA), antioxidant 1010, antioxidant 608 and anti-hydrolysis agent S9000 is changed to 100:0.04:0.5:0.3:0.3:0.5.
[0154] Polyglycolic acid B particles were collected and characterized for molecular weight using GPC. The molecular weight distribution of polyglycolic acid B was shown in the GPC curve to be a three-peak distribution. The overall weight-average molecular weight was 342,600 g / mol, and the molecular weight distribution index was 3.0. Among them, the graft copolymer showed a bimodal distribution with weight-average molecular weights of 2,949,600 g / mol and 540,680 g / mol, respectively, and molecular weight distribution indices of 1.04. The mass percentages were 4.6% and 38.6%, respectively. The weight-average molecular weight of the homopolymer was 254,000 g / mol, with a molecular weight distribution index of 1.11 and a mass percentage of 56.8%.
[0155] Melt flow rate tests on the polyglycolic acid B particles showed a flow rate of 0.2 g / 10 min at 230℃ and 2.16 kg. Melt strength tests on the polyglycolic acid B particles showed a melt strength of approximately 100 cN at 235℃.
[0156] Preparation of modified polyglycolic acid: Follow Example 1, but change the feeding rate to 2 kg / h and the residence time to about 3 min.
[0157] The melt flow rate of the modified polyglycolic acid was characterized under the following conditions: 230℃ / 2.16kg. The melt flow rate (MFR3) of the modified polyglycolic acid was 7.0 ± 1.6 g / 10 min, and the MFR1 / MFR3 ratio was 7.04, where MFR1 is the melt flow rate of polyglycolic acid A. The melt strength of the modified polyglycolic acid was also tested. At 235℃, its melt strength was approximately 3 cN, representing an increase of about 30 times.
[0158] Example 6
[0159] Preparation of polyglycolic acid B: According to Example 1, except that the ratio of glycolide, stannous octoate, ethylene-vinyl alcohol copolymer (EVOH), 1,4-butanediol, antioxidant 1010, antioxidant 608 and anti-hydrolysis agent S9000 is changed to 100:0.03:0.005:0.045:0.3:0.3:0.5.
[0160] Polyglycolic acid B particles were collected and characterized for molecular weight using GPC. The molecular weight distribution of polyglycolic acid B showed a bimodal distribution in the GPC curve. The overall weight-average molecular weight was 229,700 g / mol, and the molecular weight distribution index was 3.0. Among them, the weight-average molecular weight of the graft copolymer was 1,862,400 g / mol, the molecular weight distribution index was 1.2, and the mass percentage was 0.8%. The weight-average molecular weight of the homopolymer was 218,900 g / mol, the molecular weight distribution index was 1.7, and the mass percentage was 99.2%.
[0161] Melt flow rate tests on the polyglycolic acid B particles showed a flow rate of 12.1 ± 1.0 g / 10 min at 230℃ and 2.16 kg. Melt strength tests on the polyglycolic acid B particles showed a melt strength of approximately 1 cN at 235℃.
[0162] Preparation of modified polyglycolic acid: Follow Example 3, but change the screw speed to 120 rpm and the residence time to about 2 min.
[0163] The melt flow rate of the modified polyglycolic acid was characterized under the following conditions: 230℃ / 2.16kg. The melt flow rate (MFR3) of the modified polyglycolic acid was 16.5 ± 1.3 g / 10 min, and the MFR1 / MFR3 ratio was 3.03, where MFR1 is the melt flow rate of polyglycolic acid A. The melt strength of the modified polyglycolic acid was also tested. At 235℃, its melt strength was approximately 0.5 cN, representing an increase of about 5 times.
[0164] Comparative Example 1
[0165] The method is the same as in Example 1, except that polyglycolic acid B is replaced with polyglycolic acid A; otherwise, it is the same as in Example 1.
[0166] The molecular weight of the modified polyglycolic acid was characterized by GPC, and the analytical results are shown in Table 1. The GPC curves are shown in the figure below. Figure 1 As shown.
[0167] The melt flow rate of modified polyglycolic acid was characterized under the following conditions: 230℃ / 2.16kg. The melt flow rate (MFR3) of the modified polyglycolic acid was 18.7 ± 2.9 g / 10 min, and the MFR1 / MFR3 ratio was 2.67. MFR1 represents the melt flow rate of polyglycolic acid A. The melt strength of polyglycolic acid A was tested, and its melt strength at 235℃ was approximately 0.2 cN.
[0168] Comparative Example 2
[0169] The polyglycolic acid A to be modified was purchased from Shenzhen Boli Biomaterials Co., Ltd.
[0170] The molecular weight of the modified polyglycolic acid A was characterized by GPC, and the results are shown in Table 1.
[0171] The melt flow rate of polyglycolic acid A was characterized at 230℃ / 2.16kg. The melt flow rate (MFR1) of polyglycolic acid A was 50.0 ± 9.3 g / 10 min. The melt strength of polyglycolic acid A was tested, and its melt strength at 235℃ was approximately 0.1 cN.
[0172] Table 1
[0173]
[0174] Through Table 1 and Figure 1 The results show that the modified polyglycolic acid obtained by the interaction of polyglycolic acid B and polyglycolic acid A in the composition of the present invention not only increases the weight-average molecular weight with the amount of addition compared to polyglycolic acid A, but also shows a multi-peak distribution of molecular weight to varying degrees, that is, polyglycolic acid with a weight-average molecular weight greater than 1 million g / mol appears.
[0175] Application examples
[0176] Direct blown film tests were conducted using the modified polyglycolic acid of Example 2 and the unmodified polyglycolic acid of Comparative Example 2, respectively. The tests were performed on a Dr. Collin E30P single-screw extruder (screw diameter 30 mm, L / D ratio 30:1) and a Dr. Collin BL 180 / 600 blown film extruder. The extruder screw speed was 50 rpm, and the extruder and die temperatures were set to 180°C, 230°C, 230°C, and 235°C, respectively. The test results showed that Example 2 could successfully produce a single-layer film with a thickness of 60 μm, while Comparative Example 2 failed to form a film due to its low melt viscosity and melt strength.
[0177] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A polyglycolic acid composition, characterized in that The composition contains the following components: (a) polyglycolic acid B with multimodal molecular weight distribution; (b) Polyglycolic acid A with unimodal molecular weight distribution.
2. The composition according to claim 1, wherein In the GPC curve, the polyglycolic acid B presents a bimodal distribution or a trimodal distribution; and / or, In the GPC curve, the weight average molecular weight of at least one peak among the multiple peaks of the polyglycolic acid B is greater than 1,000,000 g / mol, and the peak area accounts for no less than 0.5%, preferably no less than 1.0%, and more preferably 1.5-10.0%; and / or, In the GPC curve, the weight average molecular weight of at least one peak among the multiple peaks of the polyglycolic acid B is 150,000 to 500,000 g / mol, accounting for no less than 50%; and / or, Under the test conditions of 230° C. / 2.16 kg, the melt flow rate MFR2 of the polyglycolic acid B is not greater than 20 g / 10 min, preferably 0.1 to 10.0 g / 10 min, and more preferably 0.5 to 5.0 g / 10 min.
3. The composition according to claim 1 or 2, wherein The polyglycolic acid B comprises a polyglycolic acid graft copolymer and a polyglycolic acid homopolymer; Preferably, at least one of the multiple peaks of the polyglycolic acid B is a polyglycolic acid graft copolymer; and / or, One of the multiple peaks of the polyglycolic acid B is a polyglycolic acid homopolymer.
4. The composition according to claim 3, wherein The polyglycolic acid graft copolymer comprises an ethylene-vinyl alcohol copolymer segment and / or a polyvinyl alcohol segment as a main chain, and a glycolic acid monomer derivative, a glycolic acid oligomer or a glycolic acid polymer as a side chain; Preferably, the structure of the polyglycolic acid graft copolymer is as shown in formula (I): In formula (I), x and m are positive integers, and y1, y2 and z are natural numbers; Further preferably, in formula (I), the sum of x, y1, y2 and z is not less than 50, preferably 50 to 6000, more preferably 200 to 2500; and / or In formula (I), m is not less than 50, preferably 50 to 1000; and / or, In formula (I), the ratio of z to x+y1+y2+z is 0-50%; and / or, In formula (I), the ratio of y1 to x+y1+y2 is 0 to 32%.
5. The composition according to claim 3 or 4, wherein The structure of the polyglycolic acid homopolymer is shown in formula (II): In formula (II), M1, M2, ..., M i Each independently n1、n2、······、n i Each is independently a natural number, and at least one is not 0, i is an integer not less than 1, R is H, an alkyl group or an aromatic group; X is any chain segment, preferably X is H or an alkyl group or an aromatic group with a carbon number not greater than 20; Preferably, in formula (II), when i is 1, R is H, an alkane group or an aromatic hydrocarbon group; and / or, In formula (II), when i is greater than 1, R is an alkane group or an aromatic hydrocarbon group having a molecular weight of 14 to 1000 g / mol; and / or, In formula (II), i is an integer between 1 and 20, preferably an integer between 2 and 6; and / or, In formula (II), n1, n2, ..., n i The sum of is not less than 50, preferably 100 to 5000.
6. The composition according to any one of claims 1 to 5, wherein The weight average molecular weight of the polyglycolic acid A is 150,000 to 250,000 g / mol; and / or, Under the test conditions of 230° C. / 2.16 kg, the melt mass flow rate MFR1 of the polyglycolic acid A is 20 to 90 g / 10 min.
7. The composition according to any one of claims 1 to 6, wherein Under the test conditions of 230°C / 2.16kg, the melt flow rate MFR3 of the composition is 0.1 to 30 g / 10min, preferably 3 to 15 g / 10min; and / or, Under the test condition of 230° C. / 2.16 kg, the ratio of the melt flow rate MFR1 of the polyglycolic acid A to the melt flow rate MFR3 of the composition is not less than 1.2, preferably not less than 3.
0.
8. The composition according to any one of claims 1 to 7, wherein The mass ratio of the polyglycolic acid B to the polyglycolic acid A is 5:95 to 90:10, preferably 20:80 to 60:40; and / or, The composition may further contain an antioxidant component, preferably the total mass ratio of the antioxidant to the polyglycolic acid A and the polyglycolic acid B is 0.01 to 3, preferably 0.1 to 1.0; and / or, The composition may further contain a metal deactivator component, preferably the total mass ratio of the metal deactivator to the polyglycolic acid A and the polyglycolic acid B is 0.1 to 3.0, more preferably 0.1 to 0.7; and / or, The composition may further contain an anti-hydrolysis agent component, and the total mass ratio of the anti-hydrolysis agent to the polyglycolic acid A and the polyglycolic acid B is preferably 0.1 to 5.0, preferably 0.3 to 3.
0.
9. A method for preparing the composition according to any one of claims 1 to 8, characterized in that: The preparation method comprises: melt-blending the components in the composition; Preferably, the conditions for melt blending include: The blending temperature is 220 to 260°C; and / or, The blending time is 0.5 to 10 minutes, preferably 2 to 6 minutes.
10. An article comprising the composition according to any one of claims 1 to 8.
11. A method for preparing the product according to claim 10, characterized in that: The preparation method comprises: heat treating and molding the composition.
12. A method for adjusting the melt flow rate of polyglycolic acid, characterized in that: The method comprises: subjecting the components in the composition of any one of claims 1 to 8 to a step including melt blending to adjust the melt flow rate of the polyglycolic acid A in the composition to obtain modified polyglycolic acid.
Citation Information
Patent Citations
Polyglycolic acid copolymer composition and preparation thereof
CN112469765A
Modified polyglycolic acid as well as preparation method and application thereof
CN114075332A
Polyglycolic acid composition as well as preparation method and application thereof
CN114075378A
Composition for preparing polyglycolic acid material, polyglycolic acid material as well as preparation method and application of polyglycolic acid material
CN115322303A
Polyglycolic acid resin particle composition and process for production thereof
CN101296994A